Fundamental limits of caching: improved bounds for users with small buffers. Issue 17 (1st November 2016) - Chen, Zhi; Fan, Pingyi; Letaief, Khaled Ben
Abstract : In this study, the caching problem is investigated. Assuming that the users are only equipped with buffer of small sizes, the peak rate of caching problem is investigated in this study. In contrast to recent results in the literature, this study shows that under some specific condition, i.e. if the number of users is no less than the amount of files in the server, a lower peak rate of caching is achievable. Furthermore, this new presented peak rate of caching is demonstrated to coincide with the well‐known cut‐set bound.